Do profitability and liquidity drive market valuations? A study based on Tobin Q in LQ45 Firms (Q1 2021 – Q3 2024) - Aditya Wardana; Rolan Mart Sasongko; Hafidh Rifky Adiyatna; Ryan Setya Budi; Ida Ayu Fatmayuni (Priviet Social Sciences Journal, 2025)
This study aims to evaluate the effect of return on assets and current ratio on firm value in LQ45 indexed companies from Q1 2021 until Q3 2024. Quantitative causal-comparative design used and a census sampling of 45 companies (675 observations), This study employs Tobin’s Q as an indicator of firm value. The analysis reveals that ROA positively and significantly influences firm value, indicating that higher profitability improves investor valuation. In contrast, there is no statistically significant relationship between CR and firm value, suggesting that liquidity is not a primary driver of market valuation. Recommendations include focusing on profitability and asset efficiency to increase firm value, while future research should explore additional variables such as firm size or leverage. The limitations of this study relate to the use of Tobin's Q as a measure of firm value, whereas other methods can also be used.